PENGARUH RATIO KEUANGAN TERHADAP KINERJA KEUANGAN PADA BANK UMUM SYARIAH - Rosada, Nurhidayati (Jurnal Ilmu Manajemen, 2013)
This study examined the effect of financial ratios proxied by CAR), ROA, NPL and financial performance LDR Islamic Banks in Indonesia are proxied by return on assets (ROA). In this study population of 3 companies, namely PT. Bank Syariah Mega Indonesia, PT. Bank Muamalat Indonesia and PT. Syariah Mandiri. From the results of the study showed that: 1) There is a significant effect between CAR, ROA, NPL and LDR together to ROA, and 2) There is a significant effect on ROA ROA partially. Implementation is avariable that can be input CAR, ROA, NPL and LDR can be used to guide, either by the management company in the management of the company, as well as by investors in determining investment strategy.